Advanced Application of Digital Technologies for Rehabilitation and Remote Monitoring of Patients with Post-Covid Syndrom: a Review - Maryana A. Ansokova; Ivan A. Rozanov; Larisa A. Marchenkova (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2023)
AIM. To describe modern technologies for telerehabilitation and remote monitoring of the condition of patients who have undergone a new coronavirus infection COVID-19, and to show the experience of the National Medical Research Center for Rehabilitation and Balneology of the in the clinical testing and development of these technologies. MATERIAL AND METHODS. A consistent analysis of 39 modern sources of scientific literature (including systematic reviews and original researches), selected by the keywords of this article and including the most up-to-date publications in rating peer-reviewed journals, allows us to conclude the following. The use of digital methods of rehabilitation and diagnostics in institutions of restorative medicine in patients who have had a new coronavirus infection can reduce the risks of undesirable outcomes and the burden on medical personnel, reduce the severity of manifestations of post-COVID-19 syndrome and improve the quality of life of patients. RESULTS AND DISCUSSIONS. The article describes the prospects for the use of modern intelligent technologies (virtual reality, biofeedback mechanotherapy and remote analysis of the cardiovascular system, motor activity and psychoemotional sphere) in the treatment and rehabilitation programs of patients who have suffered a new coronavirus infection COVID-19. The clinical aspects of the new coronavirus infection that determine the use of digital technologies and remote monitoring in the medical rehabilitation of patients with postcovid syndrome are presented. The technologies of virtual reality, biofeedback mechanotherapy and remote monitoring developed for the rehabilitation of patients with postcovid syndrome at the National Medical Research Center for Rehabilitation and Balneology are described in detail, data on their effectiveness, as well as limitations and difficulties possible with the introduction of digital methods of rehabilitation and telemedicine methods are given. The analysis of psychological factors of distress caused by a new coronavirus infection and approaches to their remote telemonitoring were carried out. CONCLUSION. The effectiveness of new digital rehabilitation methods that have recently appeared in clinical practice allows us to conclude that the use of modern intelligent technologies is promising. Among them, it should be noted such technologies as virtual reality, mechanotherapy with biofeedback and remote analysis of the performance of the cardiovascular system, motor activity and psycho-emotional sphere in the treatment and rehabilitation programs of patients with post-ovoid syndrome.